The Resilience of Sharia Consumer Protection in Digital Economy Disputes: Integrating Litigation, Non-Litigation, and Online Dispute Resolution (ODR) - Shofa Robbani; Muhammad Jauharul Maknun; Dina Anggraini; Safira Najihah (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2026)
This study aims to analyze the resilience of Sharia consumer protection in digital disputes through the roles of litigation, non-litigation, and Online Dispute Resolution (ODR). The method used is normative legal research employing legislative, conceptual, and comparative approaches, analyzed qualitatively through a literature review. The results show that digital consumer disputes are dominated by product nonconformity, unclear contracts, and fraudulent practices (tadlis), reflecting a gap between Sharia principles and digital practices. Litigation is considered ineffective due to lengthy procedures and high costs, while non-litigation methods are more flexible but limited in their implementation. ODR emerges as the most adaptive mechanism, although it remains weak in terms of regulation, independence, and the integration of Sharia principles. This study contributes by proposing a concept of legal resilience based on the integration of litigation, non-litigation, and ODR, as well as the development of a Sharia-based ODR model encompassing three main pillars: (1) a digital ishlah mechanism ensuring consensus-based and transparent resolution; (2) a panel of independent, Sharia-certified mediators; and (3) operational standards based on maqāṣid al-sharī‘ah that avoid gharar and tadlis at every stage of the process. This model emphasizes substantive justice, transparency, and the public interest in the resolution of digital disputes.